The Influence of an Anxious Mood on Human Directional Choice by Enhancing Focused Attention - Chobok Kim; Yunji Lee (Korean Journal of Cognitive and Biological Psychology, 2019)
The current study aimed to examine how the anxious mood state affects human directional choice. For this purpose, we employed a version of the spatial Stroop task and tested the effect of the induced anxious mood state on the facilitation and interference effects. In an experiment, neutral and anxious picture-and-sound sets were employed to manipulate different moods between two groups. After the mood induction, participants performed a version of the spatial Stroop task that included congruent, neutral, and incongruent trials. The results showed that an anxious mood enhanced the facilitation effect, but reduced the interference effect. In contrast, the conflict adaptation effect was not influenced by the anxious mood. These findings suggest that an anxious mood can accelerate target processing through enhancing focused attention but not inhibitory control. The practical implications for human directional choice in an evacuation situation are discussed. KCI Citation Count: 0